Utilizing Cash Flow Statement in Risk Analysis: An Analytical Study of a Sample of Iraqi Banks Registered in the Iraq Stock Exchange During the Period (2010-2019) - Saeed, Lovan A.; Faraj Qardaghi, Kawa M. (Mitanni Journal of Humanitarian Sciences, 2023)
The aim of the study is to identify the theoretical aspects and via practical side from which the preparation of the statement of cash flows and provide the necessary liquidity. In order to enable banks to know the financial position and risks analysis that they face based on the impact of strength and weakness in these statement in making investment decisions regarding operational, investment and financing activities ,Accordingly, the following hypothesis will be tested through this research Financial indicators derived from the cash flow statement can be used in analyzing financial risks in Iraqi banks registered in the Iraq Stock Exchange, to achieve the goals the descriptive and analytical approach was used by analyzing the cash flow statement indicators , financial risk indicators through a financial analysis of a sample of Iraqi banks registered in the Iraq Stock Exchange during the period (2010-2019), The current study has reached a number of conclusions, the most important of which are: The statement of cash flows is one of the most important financial statements because it provides accurate financial information due to its reliance on the cash basis, Among the most important recommendations of the research, banks should focus on using the cash flow statement and its analysis to improve profits and reduce liquidity and credit risks .